2022
DOI: 10.1371/journal.pone.0277202
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of South African caregivers disclosing to their children living with HIV: Qualitative investigations

Abstract: Awareness of Human Immunodeficiency Virus (HIV) status improves health outcomes in children living with HIV, yet caregivers often delay disclosure. This qualitative investigation explored, through observation, how 30 caregivers responded to a HIV Disclosure study conducted between 2017 and 2020 at Chris Hani Baragwanath Academic Hospital, Soweto, South Africa. Caregivers were assisted in disclosing to their children, aged 7–13 years; followed by a sub-sample of caregivers providing in-depth interviews to elabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(90 reference statements)
1
1
0
3
Order By: Relevance
“…Our findings suggest that the most effective strategy for the child’s wellbeing and health is to respect his or her wishes and find enabling ways to sustain adherence, rather than promoting disclosure against her wishes, which could lead to non-adherence and poor mental health ( 23 , 36 , 39 ). This type of consideration and nuance in deciding who to tell and providing post-disclosure counseling and support proved a critical element of peer navigation services for youth, and aligns with findings from other research in the region around effective disclosure strategies for youth ( 6 , 35 , 40 ).…”
Section: Discussionsupporting
confidence: 69%
“…Our findings suggest that the most effective strategy for the child’s wellbeing and health is to respect his or her wishes and find enabling ways to sustain adherence, rather than promoting disclosure against her wishes, which could lead to non-adherence and poor mental health ( 23 , 36 , 39 ). This type of consideration and nuance in deciding who to tell and providing post-disclosure counseling and support proved a critical element of peer navigation services for youth, and aligns with findings from other research in the region around effective disclosure strategies for youth ( 6 , 35 , 40 ).…”
Section: Discussionsupporting
confidence: 69%
“…Cuidadores de crianças soropositivas evitam revelar o diagnóstico de infecção pelo HIV, buscando protegê-las das consequências emocionais e sociais de serem portadores de uma enfermidade grave, crônica e estigmatizante (Programa Estadual DST/Aids-SP, 2008) e, portanto, muitas vezes necessitam de ajuda profissional para conseguirem revelar o diagnóstico a estas crianças (Joyce et al, 2022;Qur'aniati et al, 2022), de forma a favorecer a adesão ao tratamento e a compreensão de sua realidade, porém sem gerar traumas e revoltas. A revelação do diagnóstico deve ser feita, o mais breve possível, em conjunto com os cuidadores, em um processo contínuo, comunicando às crianças que vivem com o HIV informações claras e precisas (Ministério da Saúde, 2009).…”
Section: Discussionunclassified
“…(Bubadué et al, 2022;Castellani & Moretto, 2016;Galano et al, 2014;Programa Estadual DST/Aids-SP, 2008;Silveira, 2008). Dentre estes, a revelação do diagnóstico, ou seja, contar para o indivíduo que ele foi infectado pelo HIV, se destaca por ser uma questão extremamente complexa, que tem se tornado cada vez mais relevante na prática clínica (Negrini, 2017;Joyce et al, 2022;Silveira, 2008) e especialmente delicada quando o sujeito é uma criança.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A qualitative exploratory descriptive study carried out in the Limpopo Province, South African caregivers for CLWHIV were not trained in initiating HIV disclosure [39]. Given that, caregivers of orphaned children by HIV/AIDS who lack the ability to disclose believed that healthcare professionals should help them to conduct disclosure process [40]. Despite inadequate support, the ndings of the study conducted by Muditambi et al [39] revealed that caregivers reported that the healthcare practitioner had advised them on how to disclose HIV status to CLWHIV.…”
Section: Context (In What Context Is the Conceptual Framework Perform...mentioning
confidence: 99%